Improving The Understanding of The Religion of “Syifaul Qulub” Learning Group in Lamongan District Through Nonformal Education in The Teaching of Sunday Morning - Hana Nadia (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
This study aims to explore what underlies the influence of non-formal education on the understanding of religion in “Syifaul Qulub” learning group in Lamongan Regency. The approach used is quantitative, so far the understanding of pilgrims can be involved and understand Islam. The first variable is "non-formal education" as the independent variable and the second variable is "religious understanding" as the dependent variable. This problem needs to be studied because the author realizes that the condition of society is good if all parties have concern for the community environment where education is a necessity, religion is also the key to humans to coexist in the community. Therefore the writer takes the theoretical and empirical path. Theoretically, it examines several sources of literature, while empirically conducting field research, using methods: observation, interview, documentation, and questionnaire. The results of this study were found, at a significance level of 5% at N = 60, showing a value of 0.254, while the value of rxy obtained was: 0.421. Thus the rxy obtained was greater than the price of "r" in the Significant Level Table of 5%. While at a significant level of 1% at N = 60, the figure is 0.330, while the rxy value obtained is 0.421. Then the rxy obtained is greater than the price "r" in the table of 1% significance level. The population in this study was the “Syifaul Qulub” learning group, totaling 750 worshipers. While the sample is 60 worshipers. While analyzing the data with Random Sampling statistics. Keywords: Non-formal Education, Understanding of Religion, Syifaul Qulub